Pembelajaran Instrumen Musik Tradisional Rabab Kelas X Di SMK Negeri 7 Padang - Vivin Okprioni; Harisnal Hadi (SENDRATASIK UNP, 2019)
This article aims to know the process of learning music rabab against learning styles students use audio visual media in SMK Padang 7. This type of research is qualitative descriptive method. Object of research i.e. grade X Karawitan SMKN 7 Padang. The data obtained is collected through literature study, observation, interviews, and documentation. Results of the study is that the results of student learning is already quite good than ever before. Based on the results of the observation of learning styles, media relevant to learning is applied in the audiovisual media. Lying spirit and students in learning the music improved rabab. Students are more motivated to follow the music learning process of learning from the rabab proved that followed with active students analyze, follow, move, touches and bold things in regard to learning music rabab. It also can be proved by the increase in student learning outcomes assessment.